Analisis Pengaruh Syahbandar, Kelaiklautan Kapal, dan ISM Code terhadap Keselamatan Pelayaran: Studi Regresi di Pelabuhan Ketapang - Riztian Aditya (Port Management and Maritime Administration Journal, 2025)
Maritime safety is a crucial aspect of the maritime industry, particularly in Indonesia as an archipelagic country. Although regulations regarding maritime safety are well-established, the frequency of maritime transport accidents in Indonesia remains high (KNKT, 2019–2023). This study aims to analyze and test the partial and simultaneous effects of the Port Authority’s Role (X1), Vessel Seaworthiness (X2), and International Safety Management (ISM) Code (X3) on Maritime Safety (Y) at Ketapang Port. The research method used is explanatory quantitative with multiple linear regression analysis. The sample involved 75 respondents, including ship crew members and Port Authority officers, selected using Simple Random Sampling. The analysis results indicate that the three independent variables have a positive and significant impact on Maritime Safety. The regression model shows an adjusted R Square value of 0.610. Among the three variables, the ISM Code (B = 0.410) is the most dominant factor, followed by the Port Authority’s Role (B = 0.389), and Vessel Seaworthiness (B = 0.186). These findings highlight that structured internal safety management (ISM Code) has the highest leverage, supported by strong regulatory oversight.